Attitude of Health Workers to Immunoprophylaxis and Efficacy of Their Health Education Activities Regarding Active Immunization of the Population - O.Ye. Abaturov; O.V. Siedunova; O.O. Agafonova (Zaslavsky O.Yu., 2015)
The article presents the results of a study regarding primary care pediatricians' attitude to immunoprophylaxis and their contribution to the formation of parental attitude to vaccination. By comparing the measures carried out by physicians, and the level of vaccination coverage in their areas, we have established the most effective methods of health education activities among parents in terms of active immunization of children.